Why the Microsoft settlement won't work. - Bresnahan, T.F.
The Microsoft antitrust trial, probably the most important technology-related legal case of our time, appears to be limping at last toward a conclusion. Unfortunately, there is an excellent chance that the software colossus will win, despite losing, without much to restrain it from going back to the heavy-handed, anticompetitive tactics that prompted the antitrust action in the first place.
Keywords: Microsoft antitrust trial; Microsoft settlement; Anticompetitive tactics; Technology-related legal case